INVENTARISASI PTERIDOPHYTA DI KAWASAN WISATA TOP SELFI KRAGILAN PAKIS KABUPATEN MAGELANG DAN PEMANFAATANYA SEBAGAI MODUL PEMBELAJARAN BIOLOGI SMA - Indriyani, Wiwit; Radian, Muhammad; Sukmawati, Ika (FKIP Universitas Tanjungpura, 2024)
This research aims to determine the types and diversity of pteridophytes found in the Top Selfie Kragilan tourist area, Pakis, Magelang Regency. As well as to determine the feasibility and practicality of the biology module resulting from the inventory of ferns for use in high school learning. This research uses mixed methods, namely exploration and research and development methods which use the ADDIE research design with steps, namely Analysis, Design, Development, Implementation and Evaluation. (Evaluation). However, in this research only 4 stages were carried out without an implementation stage due to limited research time, costs and personnel. The subjects of this research consisted of pteridophyte plants, class X students of SMA N 2 Magelang, species expert validators, material experts, and also media experts. The instruments used in this research were interview sheets, observation sheets, validation sheets and practicality test questionnaires. Based on the research results, the following results were obtained: 1) Based on the results of the inventory of pteridophytes in Top Selfie Kragilan, there were 12 types of pteridophytes. 2) The results of calculating the species diversity index value (H') obtained a value of 1.5 in the medium diversity category. 3) The pteridophyta module based on the local potential of pteridophyte diversity in the Top Selfie Kragilan tourist area was declared valid and suitable for use in learning with a validity value of 3.51. 4) The practicality level of the module obtained a score of 81.71% with a practical category and suitable for use in learning.